The Testing of Autogenous Grinding in Laboratory and Pilot Scale and the Design of Full Scale Comminution Circuits - Kalapudas R; Morsky P; Virtanen M; Natunen H (The Australasian Institute of Mining and Metallurgy, 1993)
The development of autogenous grinding modification in Outokumpu, known with the name 'Outogenius Comminution', was 'reversed'. At first the metallurgists studied and tested tens of years autogenous grinding in detail in full scale circuits at the concentrators of the company. After the final solution already had been found, also a pilot plant was built and now finally, research work is under way to develop a special laboratory method for testing the suitability of ores for 'Outogenius Comminution'.